Exploring the Drivers of Voluntary Tax Compliance among MSMEs: The Role of Religiosity, Monetary Ethics, and Administrative Systems - Siska Andri Wulandari; Aryani Intan Endah Rahmawati (Scientax: Jurnal Kajian Ilmiah Perpajakan Indonesia, 2026)
The number of Micro, Small, and Medium enterprises (MSMEs) in Indonesia has increased steadily over time; however, this growth has not been accompanied by a proportional contribution to tax revenue. Both internal and external factors, including religiosity, monetary ethics, tax education, and the digitalization of tax administration systems, are considered potential determinants of MSME tax compliance. Attribution theory is used as the basis for developing hypotheses, with internal factors (religiosity and monetary ethics) and external factors (tax education and digitalization of tax administration systems) influencing behavior (voluntary tax compliance). Data were collected through questionnaires from MSME operators with a Taxpayer Identification Number (NPWP) registered with the Surakarta Cooperative and MSME Office. A total of 100 respondents were acquired through the application of purposive sampling methods. Multiple linear regression was employed to analyze the data, and the findings reveal that religiosity, tax education, and the digitalization of tax administration systems exert a positive effect on voluntary tax compliance, whereas monetary ethics show no significant influence. These findings are useful for tax authorities in developing more effective socialization strategies, focusing on enhancing religiosity and tax understanding among taxpayers.